Effects of Brine Heat Treatment Conditions on Pork Myoglobin - Jie Wu, Yong Liu, Jing Xu, Cuizhu Wu (Forest Chemicals Review)
Myoglobin, a pigment protein mainly present in the sarcoplasm, serves as a decisive factor affecting the color of meat and meat products. In order to investigate the effect of heat treatment intensity on meat color during the brine treatment process of meat products, this paper takes pork as the research object, and studies the effects of different cooking time and cooking temperature on the water retention, color and myoglobin of pork. The results showed that, the water holding capacity of pork decreased gradually with the increase of heat treatment intensity; the lightness value (L*) of pork increased first and then decreased, while a* value decreased first and then increased, and b* value fluctuated little with the increase of heat treatment intensity. With the continuous increase of cooking temperature, L* value presented a fluctuating upward trend as a whole, a* value and b* value first increased and then decreased, reaching the maximum at 80°C. Myoglobin content and the ratio of its three forms were greatly affected by the heat treatment temperature. With the increase of heat treatment intensity, the myoglobin content continuously decreased, which changed drastically when the cooking temperature was below 80°C, but tended to stabilize after 80°C. The research results provide a theoretical reference for improving and controlling the pork processing quality in the brine treatment process and improving the quality of braised pork products.